After-school sports programmes and social inclusion processes in culturally diverse contexts: Results of an international multicase study - Carter-Thuillier, Bastian; López-Pastor, Víctor; Gallardo-Fuentes, Francisco; Carter-Beltran, Juan; Fernández-Balboa, Juan-Miguel; Delgado-Floody, Pedro; Grimminger-Seidensticker, Elke; Sortwell, Andrew (Frontiers in Psychology, 2023)
This research aimed to understand the role of afterschool sports programmes in social inclusion processes in culturally diverse contexts through a multicase study within two locations. The first location was in Spain where immigrant and Spanish students were enrolled, and the other was in Chile with Mapuche-Huilliche students, immigrant and Chilean students. The implemented programmes at both sites were similar in their educational focus on socio-educational values, and teaching models (hybridization of teaching games for understanding and cooperative learning) that enhance social inclusion. Using individual and group interviews with teachers, sports coordinators, parents and students, a qualitative approach was used to identify the factors that facilitate or hinder the social inclusion processes. In addition, the researchers used qualitative observations of the programmes over six months using "notes logbook" to record their impressions during the observation process. Results indicated that the implemented sports programmes successfully facilitate social inclusion processes, enabling the development of interpersonal skills and relationships between students from different cultural backgrounds. The previous training and experiences of teachers in cultural diversity contexts, and incorporation of traditional sporting games from all cultures, seems to be an important facilitator factor for the inclusion potential of the implemented programmes.